Best Answer

3x2 + 2x - 8 = 3x2 + 6x - 4x - 8 = 3x(x+2) - 4(x+2) = (3x-4)*(x+2)

More answers

(3x - 4)(x + 2)

Q: Factor this polynomial completely 3x2 plus 2x - 8?

Write your answer...

Submit

Still have questions?

Continue Learning about Basic Math

3 * x * x * y

3x2-9x-30 =3x2+6x-15x-30 =3x(x+2)-15(x+2) =(3x-15)(x+2) OR 3(x - 5)(x+2)

(3x+1)(x+2)

3x2 + 6x is ONE expression. A common factor is a factor that is COMMON to two (or more) expressions - not just one. An alternative answer: 3x can be factored out of both of those.

(3x + 1)(x + 6)

Related questions

x3 - 3x2 + x - 3 = (x2 +1)( x - 3)

21x3-35x2+14x = 7x(3x2-5x+2)

The degree of this polynomial is 2.

If that's 3x2 + 7x + 2, the answer is (x + 2)(3x + 1)

3x2 + 27x +60

(x + 2)(3x + 1)

3x2 - 5x - 2 can be factored into (3x + 1) (x - 2)

It is a second degree polynomial.

-7

(x2 + 1)(x - 3)

3x2 + 33x + 54 =3(x2 + 11x + 18) = 3(x + 9)(x + 2)

3x2-7x-20 = (3x+5)(x-4) when factored